Brains versus Brawn: Militarization and Women in Modern Policing - Eversole, Emilee Shae (2021)
This work explores the paramilitarism that has taken policing by storm over the last few decades, the adverse effects caused by it, and what women in policing do to counteract them. Previous research has shown that some individuals believe this type of militarization of policing has severed the relationship between law enforcement officials and their communities, and false beliefs regarding the ability of women to serve as police officers seem to run rampant. However, newer research suggests that women in policing provide a refreshing contrast to this paramilitarism through less invasive tactics, resulting in a more trusting relationship between officers and the communities they serve. This work will ultimately focus on the harmful effects of the militarization of policing on the police-citizen relationship, how this also impacts female officers, and how tactics often used by women when working in policing may ultimately be one of the defining characteristics that serve to improve the police-citizen relationship